Continuing Medical Education (CME) on the Family Adoption Program - Shikha, Swati; Kumar, Abhishek; Begum, Jarina; Ali, Syed Irfan; Raj, Rohit (Indian Journal of Community Health, 2024)
The Family Adoption Program has been incorporated into the MBBS curriculum starting from the 2021-22 batch. This change in the curriculum aims to align it with competency-based medical education and ensure comprehensive coverage of cognitive, affective, and psychomotor domains of learning. The objective of the program is to enhance the accessibility of healthcare services to the rural and underserved people. This is necessary because the existing healthcare facilities in our country are primarily located in urban regions, while the rural areas have a higher concentration of population but limited health care facilities as well as poor access to healthcare. [1] A two-hour session was conducted under the banner of pre-conference CME of JHIAPSMCON 2024 on the topic- Family Adoption Program: A roller coaster ride. There were about 30 participants representing nine medical colleges of Jharkhand. The session was chaired by two faculty from an autonomous Government institution of the state. The agenda for discussion were the brief introduction on Family Adoption Program, its implementation, the role of health camp in FAP and ways in which students may be engaged in health camp and lastly the strengths, weaknesses, opportunities and challenges of the program. The intention was to share the experience of FAP implementation at Manipal Tata Medical College and also exchange of ideas and experiences by all other institutions. The perspective of faculties from other institution were also discussed. [2] There were four resource person for the session which continued one after the other with a brief discussion with the participants at the end of each sub-session.